On topological characterization of some properties of measures using Ocan typetopologies - Praninskas, Gintaras (Lietuvos matematikos rinkinys, 2010)
In the article is given topological characterization of prolongement of measure from algebra A subsets to σ-algebra subsets σ(A) as prolongement of measure as continuos function from space of subsets A to space σ(A) in some Ocan type topology. The topological of Radon and regularity of measure characterization using Ocan type topologies also is given. O топологической характеристике некоторых свойств мер посредством очановских топологий В статье дается топологическая характеристика продолжения меры, так же топологическая характеристика радоновости и регулярности мер на σ-алгебре Борелевских множеств топологического пространства посредством экспоненциальных топологий типа Очана.